Pemberian Mikroalga Terhadap Pertambahan Populasi Rotifera (Brachionus plicatilis) Pada Skala Laboratorium Di BBPBL Lampung - Aji Ara Yudha; Fitri Agustriani; isnaini . (UNIVERSITAS SRIWIJAYA, 2013)
Natural food is an important source of food in the fish breeding business. One of the zooplankton are widely used as the main feed saltwater fish breeding is a rotifer. Zooplankton rotifers is used for natural food fish, especially fish larvae are very small in size. Rotifers used in this research that Brachionus plicatilis. The purpose of this study was the effect of the accretion population Microalgae B. plicatilis and obtain the type of phytoplankton that can deliver the highest populations of B. plicatilis. The method used is the experimental laboratory with 3 treatments and 5 repetitions. The treatment used is Tetraselmis chuii, Nannochloropsis sp, and Chaetoceros sp. ANOVA one-way statistical results with a confidence level of 99% shows the effect of the treatment. Further trials with LSD showed that the increase of Nannochloropsis sp best with a maximum density of 159.8 ind / ml, followed by Chaetoceros sp the number of 118.4 ind / ml, and Tetraselmis chuii totaled 74.8 ind / ml. The high population of B. plicatilis using a feed treatment B (Nannochloropsis sp) because it has a small body size in accordance with the mouth opening B. plicatilis and high nutrient content. In this study, feeding Nannochloropsis sp produce the highest population and significant effect on population growth B. Plicatilis.Keywords: Population, Brachionus plicatilis, Tetraselmis chuii, Nannochloropsis sp, Chaetoceros sp